Money Supply Process in Malaysia - Thangavelu, Chidambaram Asary (1994)

(untitled)
The aim of this study is to examine and understand the money supply process in Malaysia since an understanding of this process is very useful not only to monetary authorities but also to all others who regard money as an important economic variable. A theoretical "monetary base-maley multiplier" model of Narrow Money Supply (M1) is formulated that expresses Narrow Money Supply as t he product of the monetary base and the money multiplier. In turn, the monetary base is stated in terms of its uses and sources While the money multiplier is expressed in terms of several component ratios, namely, the currency ratio, Bank Negara Malaysia demand deposit ratio, time deposit ratio, Government deposit ratio, statutory (required) reserve ratio and the excess reserve ratio. According to this model, the money supply process in Malaysia is influenced jointly by the policy decisions of Bank Negara Malaysia together with the portfolio decisions of commercial banks and the non-bank private sector and t he decisions of the Government with respect to the maintenance of its deposits with Bank Negara Malaysia and t he commercial banks. An empirical "monetary base-money multiplier " model of the monetary aggregate is formulated. In this model,the monetary base and each of the component ratios of the money multiplier are regressed on the economic and institutional variables that are hypothesized to affect them, respectively. The behavioural decision of the non-bank private sector represented by the currency ratio, Bank Negara Malaysia demand deposit ratio and the time deposit ratio is found to be influenced by the average personal tax rate, interest rates and the number of commercial bank offices deflated by population. The results indicate that income determines the behavioural decision of commercial banks which is reflected by their excess reserve ratio.The behavioural decision of Bank Negara Malaysia and the decision of the Government with respect to the maintenance of its deposits with t he former,represented by the monetary base, are believed to be affected by the exchange rate, foreign income, Government expenditure and the ratio of domestic interest rate to foreign interest rate.